2017
DOI: 10.1016/j.pec.2016.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma patient-provider communication about vision quality-of-life

Abstract: Objective The purpose of this study was to: (a) describe the extent to which ophthalmologists and glaucoma patients discuss vision quality-of-life during office visits, and (b) examine the association between patient and ophthalmologist characteristics and provider-patient communication about vision quality-of-life. Methods Patients with glaucoma who were newly prescribed or on glaucoma medications were recruited at six ophthalmology clinics. Patients' visits were video-tape recorded and quality-of-life comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
9
0
2
Order By: Relevance
“…As intraocular tension increased, high intraocular tension persisted. The high intraocular tension group was found with increased HSP72 expression in RGC of the right eyes and positive cells of RGC ( 1 ), but there was no significant difference of HSP72 expression in glaucoma with normal intraocular tension and primary open angle glaucoma. So, the increased expression of HSP72 in glaucoma retina had no relation with intraocular tension.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…As intraocular tension increased, high intraocular tension persisted. The high intraocular tension group was found with increased HSP72 expression in RGC of the right eyes and positive cells of RGC ( 1 ), but there was no significant difference of HSP72 expression in glaucoma with normal intraocular tension and primary open angle glaucoma. So, the increased expression of HSP72 in glaucoma retina had no relation with intraocular tension.…”
Section: Discussionmentioning
confidence: 86%
“…However, it is associated with damage of optic nerve tissue during glaucoma. So, it could be suggested that HSP72 may play a protective role in the injury of glaucoma optic nerve for cells ( 1 ). Moreover, the intensity of HSP72 immuno-staining had regional difference in retina, as well as in single RGC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O glaucoma vai progressivamente reduzindo o campo visual o que acarreta mais dificuldade para enxergar os objetos com clareza, limitando a realização das AVDs, como se alimentar, se vestir, ler, escrever e até tomar banho 5,7,11,19,23 . A falta de autonomia aumenta com o avanço da severidade da doença, de modo que quanto maior deficiência visual, mais dependência de outras pessoas, afetando as relações sociais de pacientes glaucomatosos 24,25 .…”
Section: Discussionunclassified
“…Orientar o paciente a respeito de possíveis efeitos colaterais e sobre as consequências graves da má aderência ao tratamento é fundamental para garantir o bem-estar do indivíduo. Diante disso, os profissionais de saúde precisam monitorar com regularidade a QV do paciente glaucomatoso, aplicando questionários e discutindo estratégias sobre como melhorar a QV 25,29 .…”
Section: Discussionunclassified